2020
DOI: 10.1371/journal.pone.0240254
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation was a major predictor and determinant factor of anemia in lactating women in Sidama zone southern Ethiopia: A cross-sectional study

Abstract: Anemia in women of reproductive age is highly prevalent globally and remains a public health problem. In Ethiopia, despite efforts to minimize the burden of anemia, it is still a moderate public health problem. Anemia has various etiologies including nutritional deficiency, parasitic infection, and inflammation. The aim of this study was to examine contributing factors to anemia in lactating women. Following ethical approval, and six months after delivery, all lactating women (n = 150) were recruited to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is the consequence of iron restriction due to inflammation that is mediated by the hepatic release of hepcidin, which blocks intestinal iron absorption and favors retention of iron in macrophages [11]. This increase in serum hepcidin has been used to distinguish anemia of iron deficiency from anemia of inflammation in children [12] and during pregnancy [13], but we are aware of only one other study from Ethiopia on the impact of inflammation on anemia in lactating women [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is the consequence of iron restriction due to inflammation that is mediated by the hepatic release of hepcidin, which blocks intestinal iron absorption and favors retention of iron in macrophages [11]. This increase in serum hepcidin has been used to distinguish anemia of iron deficiency from anemia of inflammation in children [12] and during pregnancy [13], but we are aware of only one other study from Ethiopia on the impact of inflammation on anemia in lactating women [14].…”
Section: Introductionmentioning
confidence: 99%
“…), and several inflammatory disorders [6]. Among these factors, iron deficiency (ID) has been reported in nearly 50% of all anemia reported worldwide [7]. Tough iron is available in nature, ID is the most common micronutrient deficiency and the leading cause of anemia [8].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that, as hemoglobin concentration increased, the size of maternal MUAC increased as well (Saaka et al, 2017a ). There is also evidence that indicated that maternal MUAC was positively associated with maternal hemoglobin as well (Gebreegziabher et al, 2020 ). Furthermore, different evidence indicated that high bioavailability of iron was found in different parts of okra (Habtamu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%